ANALISIS HUKUM ADMINISTRASI NEGARA TERHADAP MEKANISME PENETAPAN KENAIKAN GAJI ANGGOTA DPR DALAM SISTEM KETATANEGARAAN INDONESIA - Hasanah, Nurul; Anggela, Munik; Ananta Sitorus, Sakila (SIBATIK JOURNAL: Jurnal Ilmiah Bidang Sosial, Ekonomi, Budaya, Teknologi, Dan Pendidikan, 2025)
The mechanism for determining salary increases for House of Representatives members in Indonesia raises public debate amid 2025 economic pressures, highlighting issues in state administrative law compliance and constitutional system balance. This study aims to analyze the mechanism from state administrative law perspectives, its linkage to Indonesia's constitutional system, and general principles of good governance application. Employing a normative juridical approach with qualitative methods, the population comprises relevant legal norms including UUD 1945 and UU MD3, while purposive sampling selects key regulations, doctrines, and court decisions. Instruments include primary, secondary, and tertiary legal sources, analyzed through systematic interpretation, legal reasoning, and normative synthesis. Findings reveal that salary adjustments require executive coordination via Ministry of Finance and Presidential approval to meet legality, accountability, proportionality, and transparency principles, preventing unilateral legislative actions. In conclusion, robust inter-institutional checks and balances ensure public interest alignment, though empirical validation remains needed for comprehensive governance enhancement.